2010
DOI: 10.1016/j.seizure.2010.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Byproducts of protein, lipid and DNA oxidative damage and antioxidant enzyme activities in seizure

Abstract: Data on enhanced protein, lipid and DNA oxidation, together with upregulated antioxidant enzyme activities, confirm the existence of systemic oxidative stress in patients with epilepsy. It might be speculated that post-translational modification to existing functional proteins, particularly alterations to ion channels, might be at least partially responsible for acute early changes in neuronal networks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
28
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 37 publications
7
28
0
Order By: Relevance
“…We also observed slightly higher GPX level in VPA group and poly-therapy Ali M.; et al… -67-group than CBZ group although the difference was not significant. This is in agreement with others [35,36,38] . Hamed et al [5] demonstrated marked reduction in GPX levels among the untreated patients and elevated to normal levels with AED medications.…”
Section: ]supporting
confidence: 94%
See 1 more Smart Citation
“…We also observed slightly higher GPX level in VPA group and poly-therapy Ali M.; et al… -67-group than CBZ group although the difference was not significant. This is in agreement with others [35,36,38] . Hamed et al [5] demonstrated marked reduction in GPX levels among the untreated patients and elevated to normal levels with AED medications.…”
Section: ]supporting
confidence: 94%
“…Glutathione peroxidase in our patients was significantly higher than those in the control group. This is in agreement with several studies [11,35,36,37] . We suggest that GPX upregulation, in patients with epilepsy receiving AEDS, might be a consequence of induced GPX synthesis in the liver as a compensatory mechanism for decreased glutathione levels in the same group of patients.…”
Section: ]supporting
confidence: 94%
“…Sometimes, inside the normal cells, oxidation reactions release uncontrolled reactions and produce unstable oxygen molecules "free radicals". These produced compounds will react with many different important molecules in vital organs like lipid, protein, and DNA forming a new compound that damage DNA (Ercegovac et al, 2010). Antioxidants are the first line of defense against free radical damage and are critical for maintaining optimum health (Lobo et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…The important role of oxidative stress and reactive oxygen species (ROS) in seizure disorders has emerged in the last decade (1)(2)(3)(4). Still, the question of whether oxidative stress is a cause or a consequence of seizure remains unanswered.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it has been reported that increased generation of free radicals or reduced activity of antioxidative defense mechanisms can cause some forms of epilepsy and, in addition, increases the risk of seizure recurrence (2,(5)(6)(7). On the other hand, there are several experimental and clinical studies showing that seizure results in free radical production and oxidative damage to proteins, lipids and DNA (4,8,9).…”
Section: Introductionmentioning
confidence: 99%